(untitled) (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile and evaluate the clinical outcomes of patients with multidrug-resistant tuberculosis in the state of Santa Catarina, notified between 2009 and 2019. Methods: A cross-sectional observational study, using the “Sistema de Informação de Tratamentos Especiais da Tuberculose” (SITETB) database, which included all reported patients with multidrug-resistant tuberculosis in Santa Catarina state between January 2009 and December 2019. Results: Among 265 participants, the most prevalent sociodemographic characteristics were age between 20 and 59 years (90.2%), male (69.8%), white ethnicity (85.2%) and with 7 or fewer years of schooling (65.6%). There was a greater number of notifications in regions outside of Grande Florianópolis (66.4%), unsalaried patients (58.5%), with a predominance of pulmonary (91.6%) and non-bilateral (56.2%) clinical forms, with complete treatment (69.8%). The most prevalent comorbidities were the use of illicit drugs (23.4%), smoking (30.9%), alcoholism (23.8%), AIDS (16.6%) and Diabetes Mellitus (9.5%). Regarding clinical outcomes, there was statistical significance in the association of ethnicity (p=0.020) and education (p=0.009) with the clinical outcome “complete treatment”. Conclusions: The patients’ profile is mostly composed of men, of white ethnicity, between 20 and 59 years old, with 7 or fewer years of schooling, unsalaried, reported in regions outside of Grande Florianópolis, with pulmonary and non-bilateral clinical form, who completed the treatment.